Development of a low cost, microwave-type rice yield monitor with wireless data communication for rice combine harvester - Oh, Yun Ju (2011)
This study was carried out to develop a simple, portable, and rugged microwave-type yield monitoring system that could be directly used onto a conventional grain type combine harvester to monitor and record in real-time harvested rice yield. Crop yield monitor and grain moisture content by the impact-type flow sensor and capacitance-type sensor on the combine harvesters had been widely reported to be low in accuracies by previous researchers. This newly developed instrumentation system consists of a National Instrument CompactRio 9004 embedded system with NI 9221 I/O module, a National Instrument 2016 touch panel component (TPC), a Trimble AgGPS 132 DGPS, a D-link 655 with 3 D-link ANT24-0700 antennas, and a Panasonic CF-19 toughbook with D-link DWA-140 USB adapter, and related measurement sensors. Ultrasonic displacement sensors, electromagnetic rotation detector, microwave solid flow sensor and microwave moisture sensor were respectively used for measuring the combine cutting width, combine rotational elevator speed grain flow and grain moisture content going into the combine tank during the harvesting operation. Laboratory Virtual Instrument Engineering Workbench (LabVIEW) 8.6 software was programed to process and display the measured signals from the available sensors in the embedded system on-board the combine harvester and consequently display and store the transmitted signals from embedded system in the toughbook at the ground work station. Laboratory calibrations on the respective sensors showed good measurements linearity having correlation coefficients closed to 1.000. Field wireless transmission check-up between the embedded system and the toughbook showed excellent communications without data losses to a maximum distance of 140 m. Field demonstration tests on the developed yield monitoring system on-board the Clayson 1545 New Holland combine harvester in actual field harvesting operations on two rice plots for two crop growing seasons showed that the system could measure, display and record successfully the intended crop and combine performance parameters. Finally, these recorded data in the toughbook could download successfully at the laboratory and consequently utilised by ArcGis 9.2 software to generate maps of combine tracking,combine cutting width, combine elevator rotational speed, combine travel speed, instantaneous crop yield, combine field capacity, and grain moisture.